A Click-Chemistry Approach to New, Potentially Substituted Chemical Structure, Synthesis, And In Vitro Antimicrobial, Cytotoxic, And Antifungal Activity of Novel Chromene Derivatives - Sankhe, Sharad; Kamble, Prashant (International Journal of Membrane Science and Technology, 2023)
A group of chromene derivatives, labeled as 4a-c, were produced by a three-step process using sodium carbonate as a catalyst. The experiment used a solvent mixture consisting of 96% ethanol and water, with a volume ratio of 1:5. A successful reaction between the corresponding hydroxyl chromenes derivatives and propargyl bromide resulted in the propargyl ether compounds 5a-c, which are derived from chromene-3-carbonitriles. 4H-chromene-chlorophenyl conjugates 7a-c were produced by 1H-1,2,3-triazole-tethered click chemistry with propargyl ethers 5a-c and 1-azido-2-chlorobenzene. Copper ions were the most effective catalysts for these chemical reactions. The yields of 1H-1,2,3-triazole varied between 75% and 80%. The antimicrobial activity of all three triazoles (a-c) was studied in vitro. In the study conducted by MCC in 2010, four compounds were found to be effective against B. subtilis, four against S. aureus, four against P. aeruginosa, and five against E. coli.